Development of Tool to Measure the Farmers’ Perception towards Dairy-Based Farmer Producer Companies - Kumar, Sunil; Sankhala, Gopal; Kar, Priyajoy (Indian Journal of Extension Education, 2021)
A scale to measure the perception towards dairy-based farmer producer companies (FPC)Â in India was developed. A list of positive and negative (70:30) items related to the perceptionÂ towards dairy-based FPCs was prepared based on fourteen criteria advocated by Edward (1969), and 40 such items were got rated by 60 experts with massive knowledge in the field of farmer producer companies. For calculating the scale value, the score of each item was calculated based on an individual expertâ€™s score. The scale took into account theÂ maximum twenty-five percent of total item value with the maximum score and the bottommost twenty-five percent of total item value with the bottom-most score. Finally, the t value was calculated and the items having an at-value of more than 1.75 were selected andÂ incorporated into the final schedule. Based on the calculated values, 36 items were selected and finally, the scaleâ€™s reliability is 0.862 and validity is .0844 for the consistency of the results.